2018
DOI: 10.1002/fsn3.775
|View full text |Cite
|
Sign up to set email alerts
|

Potential of three probiotic lactobacilli in transforming star fruit juice into functional beverages

Abstract: The star fruit is popularly cultivated and consumed in Southeast Asia due to its high antioxidant capacity and various nutrients. In this study, three commercial probiotic strains (Lactobacillus helveticus L10, Lactobacillus paracasei L26, and Lactobacillus rhamnosus HN001) were evaluated in star fruit juice fermentation and all strains grew well with the final cell counts of around 108 CFU/ml. The star fruit juice fermented by L. rhamnosus produced the highest amount of lactic acid, resulting in a significant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(26 citation statements)
references
References 32 publications
(47 reference statements)
0
22
0
1
Order By: Relevance
“…The levels of lactic acid by L. rhamnosus ATCC 9595 in bacuri juice were comparable to other L. rhamnosus strains grown in juices. For instance, L. rhamnosus HN001 produced a higher level of lactic acid (4.4 g/L) when cultivated in star fruit ( Averrhoa carambola ) juice [ 9 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The levels of lactic acid by L. rhamnosus ATCC 9595 in bacuri juice were comparable to other L. rhamnosus strains grown in juices. For instance, L. rhamnosus HN001 produced a higher level of lactic acid (4.4 g/L) when cultivated in star fruit ( Averrhoa carambola ) juice [ 9 ].…”
Section: Resultsmentioning
confidence: 99%
“…Probiotics are commonly found in dairy foods, such as milks, yogurts and cheeses [ 4 , 7 , 8 ]; however, fruit juices may also be excellent vehicles for development of probiotic products due to their nutritional properties and presence of bioactive compounds (vitamins, phenolic acids, flavonoids and other anti-oxidant compounds) [ 9 , 10 , 11 ]. The use of fruit juices containing probiotics also gives opportunities to individuals with specific conditions (lactose intolerance, allergy to milk components and vegetarians) to benefit from the consumption of these bacteria [ 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…Fermented of poto poto (a Congolese fermented maize product), palm wine are also acidic (Abriouel et al, 2006;Abriouel et al, 2007). The fermentation of peanaple juice (Nguyen et al, 2019) and star fruit juice fermentation are also acidic (Lu et al, 2018). At this pH, there are larger microorganism populations especially represented by Lactobacillus spp, Bacillus spp and yeast that can easily grow (Ouoba et al, 2010;Abriouel et al, 2006;Abriouel et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Fermentation of juiced carried out using probiotic bacteria individually showed cell yields of, 7.2, 7.25, 7.06, and 7.16 log (cfu/mL h) Bifidobacterium lactis Bb-12, Bifidobacterium longum Bb-46, Lactobacillus casei 01, and Lactobacillus acidophilus La-5 strains, respectively, while juice fermented by a mixed bacteria culture a higher cell yields was observed. Study [67] evaluated the ability of star fruit which is popular in Southeast Asia to support the growth and viability of three commercial probiotic strains, Lactobacillus helveticus L10, Lactobacillus paracasei L26, and Lactobacillus rhamnosus HN001, showing that all strains grew well with the final cell counts of around 10 8 cfu/mL. A recent study by [61] showed that pineapple juice can be used for the production of probiotic beverage with probiotic bacteria Lactobacillus and Bifidobacterium.…”
Section: Fruits and Vegetablesmentioning
confidence: 99%